WIRELESS NETWORKED CONTROL SYSTEM WITH LINEAR SWITCHED SYSTEM - SALMA (NIM : 10108045); Pembimbing : Prof. Dr. Roberd Saragih, HABIBA
In the modern industrial world has happened a change from the manual control system to the computer-based automatic control system which is more effective and efficient. The advantages of the Networked Control System (NCS) are easy in the installation and maintenance, flexible, and low cost. But unfortunately, there is time-delays that can cause the degradation of the stability and the performance of NCS itself. The main problem in this final project is to design the controller system for a NCS plant with switched system therein. The objective of the control system is to stabilize the closed-loop system. The stability of the closed-loop system can be obtained by using the Lyapunov method, and the control system performance is measured by H2 norm values of the closed-loopÃ‚Â’s transfer function. The process for determining the control system can be written in the Linear Matrix Inequality (LMI). For verification of the obtained control system, simulation performed by applying to the DC motor system. From the simulation result, we obtain that the response time graphs of each state on the DC motor simulation show that when the input control voltage applied, the values of the current, the angular velocity, and the angular displacement are toward stability.